2014
DOI: 10.1002/jcc.23792
|View full text |Cite
|
Sign up to set email alerts
|

Pentaatomic planar tetracoordinate silicon with 14 valence electrons: A large-scale global search of SiXnYmq (n + m = 4;q = 0, ±1, −2; X, Y = main group elements from H to Br)

Abstract: Designing and characterizing the compounds with exotic structures and bonding that seemingly contrast the traditional chemical rules are a never-ending goal. Although the silicon chemistry is dominated by the tetrahedral picture, many examples with the planar tetracoordinate-Si skeletons have been discovered, among which simple species usually contain the 17/18 valence electrons. In this work, we report hitherto the most extensive structural search for the pentaatomic ptSi with 14 valence electrons, that is, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…So far, we demonstrated the stability of ptSi molecules and showed that the π electron transfer from the peripheral ring to the central vacant Si 3p z orbital is the origin of the molecular stability. Here, we compared Si‐16–5555 with the experimentally validated ptSi compound, calix[4]pyrrole silicate, [7f] the structure of which is shown in the left of Figure 6 a (for the sake of simplicity its methyl group was replaced with a hydrogen atom). In this compound, we found a highly similar MO diagram and bonding pattern to the HOMO and LUMO+3 in Si‐16‐5555, that is, the Si 3p z is mainly involved in two MOs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, we demonstrated the stability of ptSi molecules and showed that the π electron transfer from the peripheral ring to the central vacant Si 3p z orbital is the origin of the molecular stability. Here, we compared Si‐16–5555 with the experimentally validated ptSi compound, calix[4]pyrrole silicate, [7f] the structure of which is shown in the left of Figure 6 a (for the sake of simplicity its methyl group was replaced with a hydrogen atom). In this compound, we found a highly similar MO diagram and bonding pattern to the HOMO and LUMO+3 in Si‐16‐5555, that is, the Si 3p z is mainly involved in two MOs.…”
Section: Resultsmentioning
confidence: 99%
“…crystalized the structure of 1,3‐disila‐2‐oxyallyl‐borane adduct, which may be regarded as a rare case of ptSi molecules at room temperature [7e] . Furthermore, molecular clusters with 18 or 14 valence electrons SiAl 4 2− (18 e), SiIn 4 2− (18 e), SiC 2 Li 2 (14 e), HSiAl 3 (14 e), Ca 3 SiAl − (14 e), and Mg 4 Si 2− (14 e) were predicted to have a stable ptSi structure based on extensive theoretical calculations, [7f] and the tendency to form a planar tetracoordinate silicon is governed by the competition between the aromaticity and covalency in these clusters [9] . Significantly, the effect of a central planar tetracoordinate silicon was most recently confirmed experimentally in a methyl‐calix[4]pyrrole hydridosilicate, which is responsible for the remarkable stability of an anionic silicon hydride [7g] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various ptC species or molecules have been realized experimentally or designed computationally. Furthermore, the concept of ptC bonding has also been extended to planar hypercoordinate carbon (phC) and planar bonding arrangements of heteroatoms and transition metals …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the concept of ptC bonding has also been extended to planar hypercoordinate carbon (phC) [10][11][12][13][14][15][16] and planar bonding arrangements of heteroatoms and transition metals. [17][18][19][20][21][22][23][24][25][26] In addition to finding small species or molecules featuring phC(s), chemists have also explored whether the phC bonding could be applied to construct large molecular structures or bulky solids. Surveying previous studies, the reported large molecular structures/solids can be classified into three classes as summarized below.…”
Section: Introductionmentioning
confidence: 99%